Studies on Chemical Characterization of Ginkgo Amillaria Oral Solution and Its Drug–Drug Interaction With Piceatannol 3′-O-β-D-Glucopyranoside for Injection - Yu, Zhenyan; Hu, Xiaohan; Zhou, Lin; Chen, Huliang; Xing, Yanchao; Han, Chunyue; Ding, Hui; Han, Lifeng; Pan, Guixiang; Fu, Zhifei (Frontiers in Pharmacology, 2022)
Ginkgo Amillaria oral solution (GAO) is commonly used for the treatment of cardiovascular and cerebrovascular diseases in China. Piceatannol-3′-O-β-D-glucopyranoside for injection (PGI) is mainly used for the prevention and treatment of ischemic cerebrovascular diseases. With the spread of cerebrovascular disease, the possibility of combining the two drugs has increased; however, there is no research on the drug–drug interaction (DDI) between these two medicines. In this paper, an ultrahigh-performance liquid chromatography/quadrupole–orbitrap mass spectrometry (UHPLC/Q-Orbitrap MS) method was established to characterize the chemical constituents of GAO first; 62 compounds were identified or tentatively identified based on their retention time (RT), MS, and MS/MS data. Nine main compounds were determined by ultrahigh-performance liquid chromatography/triple quadrupole mass spectrometry (UPLC-QQQ-MS). Furthermore, incubation with liver microsomes in vitro was fulfilled; the results showed that GAO had a significant inhibitory effect on UGT1A9 and UGT2B7 (p < 0.05), and PGI was mainly metabolized by UGT1A9. The identification results of in vivo metabolites of PGI showed that PGI mainly undergoes a phase II binding reaction mediated by UDP-glucuronosyltransferase (UGT) and sulfotransferase (SULT) in vivo. Therefore, pharmacokinetic studies were performed to investigate the DDI between GAO and PGI. The results showed that the AUC (p < 0.05) and T1/2 (p < 0.05) of PGI in vivo were significantly increased when administered together with GAO, whereas the CL was significantly decreased (p < 0.05). The exploration of in vitro and in vivo experiments showed that there was a DDI between GAO and PGI.